Modern radio production : production, programming and performance - Hausman, Carl (Wadsworth series in broadcast and production, 2013)
MODERN RADIO PRODUCTION, NINTH EDITION, is a current, comprehensive look at radio production and programming that integrates cutting-edge technologies with explanations of traditional equipment and practices. A clear writing style, excellent descriptions and explanations, and attention to detail make this book easy to read and understand